Multiple Approaches to Identifying Key Genes Linked to the Anti-inflammatory Effects of Ginsenosides - Xiang, Gui-Fang; Zhou, Fei-Ran; Cui, Chun-Yan; Liu, Qing; Mao, An-Qiong; Zhang, Ying (Current Bioinformatics, 2025)
Ginsenoside is a naturally occurring active ingredient in ginseng, which mainly consists of four components, including Rb1, Rb2, Rc, and Rd, which are considered to be an important part of ginseng's medicinal effects. Ginsenosides can enhance the anti-fatigue ability of the body, regulate immune function, improve cardiovascular function, and have anti-aging, antioxidant, and neuroprotective effects. In recent years, many studies have found that ginsenosides have anti-inflammatory properties and are used in the treatment of many inflammatory diseases, such as endodontitis, bronchitis, and many others. Ginsenosides reduce inflammation by suppressing the release of inflammatory mediators, modulating inflammatory signaling pathways, scavenging free radicals, and modulating the immune system in a variety of ways. However, existing studies have not investigated the specific genes underlying the inflammation-reducing properties of ginsenosides. In this study, we analyzed two publicly accessible datasets from the GEO database (GSE255672 and GSE173990) to investigate the molecular basis of the anti-inflammatory effects of ginsenosides. This study aims to advance our understanding of how ginsenosides exert their anti-inflammatory properties, providing preliminary findings for identifying gene targets for their anti-inflammatory effects, thereby enhancing our understanding of their biological function and identifying new therapeutic pathways in the management of inflammation. It paves the way for further research of ginsenosides and therapeutic application of inflammation-related diseases.
Keywords: biological function